2018
DOI: 10.5479/si.1943-6696.650
|View full text |Cite
|
Sign up to set email alerts
|

American Recent Eulipotyphla: Nesophontids, Solenodons, Moles, and Shrews in the New World

Abstract: Woodman, Neal. American Recent Eulipotyphla: Nesophontids, Solenodons, Moles, and Shrews in the New World. Smithsonian Contributions to Zoology, number 650, vi + 107 pages, 27 figures, 1 table, 4 appendixes, 2 indexes, 2018.-The mammalian taxonomic order Eulipotyphla comprises the living families Erinaceidae (gymnures, hedgehogs, and moonrats), Solenodontidae (solenodons), Soricidae (shrews), and Talpidae (desmans and moles), as well as the recently extinct Nesophontidae (nesophontids). Morphological and molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 142 publications
(365 reference statements)
0
15
0
Order By: Relevance
“…1). This is a well-known historical locality for collecting fossils, insects, and mammals (Fairchild 1980;Borroto-Paéz et al 2012;Velazco et al 2013;Woodman 2018;Núñez-Novas et al 2019); however, very few herpetological surveys have been conducted there.…”
Section: Reptiles and Amphibians C O N S E R V At I O N A N D N At U R A L H I S T O R Ymentioning
confidence: 99%
“…1). This is a well-known historical locality for collecting fossils, insects, and mammals (Fairchild 1980;Borroto-Paéz et al 2012;Velazco et al 2013;Woodman 2018;Núñez-Novas et al 2019); however, very few herpetological surveys have been conducted there.…”
Section: Reptiles and Amphibians C O N S E R V At I O N A N D N At U R A L H I S T O R Ymentioning
confidence: 99%
“…Traditionally, the water shrew Sorex palustris was considered to occur throughout much of the boreal zone of Alaska and Canada, with southern extensions of range in the Appalachian Mountains in the east and the Sierra Nevada, Great Basin, and Rocky Mountain ranges in the west (Hall 1981). However, based on molecular data, Hope et al (2014) demonstrated that S. palustris was actually composed of three distinct clades, with eastern populations referred to Sorex albibarbis, boreal populations referred to S. palustris, and western ''cordilleran'' populations referred to S. navigator, the Rocky Mountain water shrew (Woodman 2018). Subsequently, Nagorsen et al (2017) demonstrated the morphological distinctiveness of S. palustris and S. navigator.…”
Section: Introductionmentioning
confidence: 99%
“…in the past decade (e.g., Woodman 2015Woodman , 2018Woodman , 2019Zeballos et al 2018), the number of species in the genus might not be well-known due to the difficulty in collecting shrews, the relatively low representation of specimens in natural history museums, and the lack of taxonomic experts (Carraway 2007;Woodman et al 2012).…”
mentioning
confidence: 99%
“…Cryptotis goodwini (sensu lato) had been considered widely distributed. More recently it was shown to be composed of several independent lineages recognized as distinct species (namely C. cavatorculus, C. celaque, C. eckerlini, C. goodwini, C. lacertosus, C. magnimanus, C. mam, C. matsoni, C. mccarthyi, C. montecristo, and C. oreoryctes;Woodman 2010Woodman , 2018Woodman , 2019. In addition, C. griseoventris is part of this species group (Woodman 2018).…”
mentioning
confidence: 99%
See 1 more Smart Citation